ENHANCING STUDENTS’ PROFICIENCY IN SUBJECT-VERB AGREEMENT USING “QUIZWHIZZER” AS A PEDAGOGICAL TOOL: CLASSROOM ACTION RESEARCH - Adawiyah, Ratna Marwa; Yani, Ani (IJIET (International Journal of Indonesian Education and Teaching), 2024)
This study examines the effectiveness of applying QuizWhizzer in enhancing students’ proficiency in comprehending subject-verb agreements in the simple present tense. This study is crucial to improve Students' comprehension of subject-verb agreement in the simple present tense. This comprehension serves as a vital foundation for students to compose high-quality written work, ultimately enhancing their academic and professional capabilities in the future. The participants in this research consisted of 28 junior high school students. The research employed a collaborative classroom action research approach (CAR). Data collection utilized pre-test and post-test results conducted within each cycle, researcher-conducted observations, and assessment sheets completed by colleagues. The collected data were analyzed quantitatively. Quantitative results indicate a significant improvement during this study's pre-cycle, cycle I, and cycle II phases. The average score increased from an initial 6.1 to 39.6 in cycle I and further to 74.3 in cycle II. These findings indicate that the utilization of QuizWhizzer in learning English grammar, especially on the topic of Subject-Verb Agreement in Simple Present Tense, is effective in increasing students' comprehension.